The health and economic impact of acute gastroenteritis in Belgium, 2010–2014. (2019) - Papadopoulos, Theofilos; Klamer, Sofieke; Jacquinet, Stephanie; Catry, Boudewijn; Litzroth, Amber; Mortgat, Laure; Mamouris, Pavlos; Rebolledo, Javiera; Vaes, Bert; Van Cauteren, Dieter; Van der Heyden, Johan; Beutels, Philippe; et al.
Abstract: Acute gastroenteritis (AGE) remains a common condition in both low- and high-income countries. In Belgium, however, there is currently a lack of information on the societal health and economic impact of AGE. We conducted a retrospective study using mortality and cause-of-death data, hospital data, primary care data, health interview survey data and other published data. We estimated the burden of illness during a 5-year period (2010–2014) in Belgium in terms of deaths, patients admitted to hospitals, patients consulting their general practitioner (GP) and cases occurring in the community. We further quantified the health impact in terms of disability-adjusted life years (DALYs) and the economic impact in terms of cost-of-illness estimates. We estimated 343 deaths, 27 707 hospitalised patients, 464 222 GP consultations and 10 058 741 episodes occurring in the community (0.91 cases/person) on average per year. AGE was associated with 11 855 DALYs per year (107 DALY per 100 000 persons). The economic burden was estimated to represent direct costs of €112 million, indirect costs of €927 million (90% of the total costs) and an average total cost of €103 per case and €94 per person. AGE results in a substantial health and economic impact in Belgium, justifying continued mitigation efforts.